Desempenho e emissões de um motor agrícola ciclo diesel utilizando misturas de óleo diesel, biodiesel e etanol - Bertinatto, Rovian (2021)
Blends of mineral diesel oil, biodiesel and ethanol are strategies for partial replacement of fossil fuel, applicable in compression ignition engines, without major adaptations. In this work, two bibliometric analyzes were carried out on the use of blends of: diesel oil and ethanol (D:E) and diesel oil, biodiesel and ethanol (D:B:E), in engines with electronic injection management and gas treatment system with Exhaust Gas Recirculation (EGR) valve. In addition, experimental evaluations were carried out on an agricultural multi-cylindrical compression-ignition engine, turbocharged with aftercooler, electronic injection management and EGR gas treatment system. In the experimental evaluations were used Diesel oil of low (BS10 -10 ppm) and high sulfur content (BS500 - 500 ppm), with 10% biodiesel in its constitution, blended with anhydrous ethanol with additives at concentrations of 5%, 10%, 15% and 20%, totaling eight tested fuels and two reference conditions (without ethanol). The average and maximum values of the engine performance parameters, fuel consumption and gas emissions (CO, HC, NOx, HC + NOx and MP) were evaluated according to the ABNT NBR ISO 8178-4 standard. The bibliography indicates that for most works published the D:E blends demonstrate an increase in specific fuel consumption and the reduction of PM emissions. On the other hand, the results of the D:B:E mixtures show that there was an increase in specific fuel consumption, an increase in CO and HC emissions (mainly in low and medium loads), and a decrease in NOx and PM emissions. As a result of the tractor’s performance test, was observed that as the ethanol concentrations increase, torque and power decrease, and hourly and specific consumption increase, for both fuels (BS10 and BS500). The exception occurred for the BS500 with 5% ethanol, which showed 0.62% higher results for torque and 0.57% for power, compared to pure BS500. Besides, the specific fuel consumption showed no difference for the 5% ethanol concentration compared to the BS10 and BS500 pure fuels. When analyzing the maximum performance of the engine, the increase in ethanol concentrations decrease the maximum torque and maximum power. The consumption results in the ABNT NBR ISO 8178-4 operating modes, on the other hand, occurred differently from those obtained in the dynamometer test at full load, as there was no direct relationship between the increase in ethanol concentrations and the increase in consumption time and specific fuel. For gas emissions, as increase ethanol concentrations in the blends, there was an increase in CO, NOx and HC + NOx emissions, and a reduction in PM emissions. HC emissions were not directly related to the increase in ethanol concentrations. CO and PM emissions do not exceed the limit values of the MAR-1 standard, even at 20% ethanol concentration; however, HC + NOx had a value below the limit only for fuels without ethanol, the remaining emissions are above the limit.